Maternal nutritional intervention for preeclampsia prevention: Integrating video-based education and local fish cooking workshops - Dea Anenta Veonika; Tia Wida Ekaputri Hz; Niken Irfa Nastiti; Annissa Delfira; I Made Dwi Mertha Adnyana (Community Empowerment, 2026)
Preeclampsia remains a primary driver of maternal mortality in Indonesia, highlighting the urgency of addressing maternal nutritional status as a critical, modifiable risk factor through targeted community programs. This community service aims to elevate pregnant women's literacy regarding balanced prenatal nutrition for preeclampsia prevention while mapping their baseline nutritional profiles and risk factors. The program integrated comprehensive health screenings (anthropometric and blood pressure measurements, and medical history assessments) with interactive video screenings and hands-on cooking demonstrations featuring local fish resources. Clinical screenings revealed a high prevalence of metabolic risks: 40% of participants were obese and 35% presented with anemia. A remarkably strong positive correlation was observed between BMI and MUAC (r=0.788; p<0.001). Post-intervention assessments demonstrated a substantial surge in nutritional knowledge, most notably regarding calcium requirements (131.6%) and protein needs (104.8%). Ultimately, combining visual education with experiential cooking workshops serves as an effective, highly practical strategy to improve maternal nutritional literacy and reinforce preeclampsia prevention frameworks at primary healthcare levels.